PENINGKATAN KUALITAS DAN PRODUKTIFITAS KRIPIK PISANG DENGAN MESIN PERAJANG DI DESA JATI KECAMATAN UDANAWU KABUPATEN BLITAR - Mohammad Muhsin; Nanang Suffiadi Ahmad (ADIMAS Jurnal Pengabdian Kepada Masyarakat, 2017)
Has been implemented community service program in Desa Jati Kecamatan Udanawu kabupaten  Blitar with the main partner of “keripik pisang” (banana chips) home industry. Implementation of the program focused on efforts to overcome the problems of the partners is low production capacity because it is still done manually. In addition, the quality of the product is also still low, not uniform thickness of the resulting chips. Solutions provided to partners in the form of a chopper machine capable of producing chips with a capacity of 12 kg / hour and an average thickness of 3 mm. The results obtained from the implementation of this program is the improvement of capacity and product quality. In addition, the entrepreneurship motivation of the partners has increased after previously experiencing difficulttimes.